Using intelligent agent in electronic bulletin board system / Shahrizan Uyo @ Shahrizan Shapiee - Uyo, Shahrizan (2006)
The research is about using intelligent agent in bulletin board system. This intelligent agent will provide useful information and instruction to the users in an interactive way and also displaying useful information about the system. The development of the intelligent agent is to change the traditional interface of the websites that are so much inhuman into an artificial life that can interact with the users. The main objectives of the research is to identify characteristic and the features of current bulletin board based on literature review, determine which intelligent agent that can be used within the bulletin board system and identify information that can be displayed by the virtual assistant intelligent agent. The scope of the project is including the development of the intelligent bulletin board prototype. The researcher have done some review of literature on previous research that very important to the development of this research. The development of the system will use the System Development Life Cycle (SDLC) approach. This approach includes system planning, system analysis, system design and implementation. The development of the intelligent agent is based on several artificial intelligent functions including natural language processing, document summarization, document indexing and knowledge base generation. The findings that can be gain by this research is the similarities and the differences between several top user rated bulletin board and the user's acceptance towards the intelligent agent features. So, in conclusion, the researcher sees that the intelligent bulletin board will be well accepted and used by the users. For further research, it is recommended for the next researcher to focus more on other type of intelligent software agents besides virtual assistant agents such as filtering agents or web agents to be implemented not only in the bulletin board system, but also in other websites generally.